PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN UTANG SERTA PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Arthur Simanjuntak (Methosika: Jurnal Akuntansi dan Keuangan Methodist, 2017)
The objective of the research was to examine the influence of profitability and credit policy on company value with dividend policy and decision to invest as intervening variables in manufacture companies listed in BEI (Indonesia Stock Market) in the period of 2012-2016. The research used causal research method. The population was 136 manufacture companies listed in BEI in the period of 2012-2016, and 95 of them were used as the samples, taken by using purposive sampling technique. The data were analyzed by using path analysis. The result of the research showed that the variables of profitability and credit policy simultaneously had influence on company value. Partially, profitability (ROA) had negative and insignificant influence on company value, profitability (ROE) had negative but significant influence on company value, profitability (ROI) had had positive and significant influence on company value, profitability (NPM) had positive but insignificant influence on company value, and credit policy had negative and insignificant influence on company value. The variables of credit policy were good intervening variables for profitability (ROA, ROE).